Respuestas

2012-08-13T00:54:01+02:00

        SenXCosY+SenYCosX+SenXCosY-CosXSenY

       --------------------------- -------------------------

                     CosXxCosY


             2SenXxCosY

         -----------------------=2Tan

               CosXxCosY

2012-08-13T02:06:24+02:00

Sen(x+y) + Sen(x-y)
--------------------------------=
Cosx * Cosy

senx*cosy+seny*cosx+senx*cos(-y)+sen(-y)*cosx
----------------------------------------------------------------------=
Cosx * Cosy

senx*cosy+seny*cosx+senx*cosy-seny*cosx
----------------------------------------------------------------------=
Cosx * Cosy

senx*cosy+senx*cosy
-------------------------------=
Cosx * Cosy

2senx*cosy
-----------------=
Cosx * Cosy

2senx
----------=2tanx
Cosx 

por lo tanto:

Sen(x+y) + Sen(x-y)
--------------------------------=2tanx
Cosx * Cosy